The public sphere: liberal modernity, catholicism, Islam - Salvatore, Armando (Culture and religion in international relations, 2007)
Introduction: The genealogy of the public sphere -- Religion, civilization, and the redefinition of tradition -- Bridging imagination, practice, and discourse -- The public reason of the commoner -- The collective pursuit of public weal -- The implosion of traditions and the redefinition of common sense -- The modern public sphere: transforming practical reason into prudential communication -- Conclusion: After genealogy: towards a pluralist theory of the public sphere